COLLABORATION FOR THE PRESERVATION OF SUNDANESE DANCE CULTURE IN THE DEVELOPMENT OF DANCE ART CURRICULUM AT LKP BINA LESTARI SUMEDANG - Heryono, Heri; Zuraida, Ida; Astarina, Atri Nadia; Hendar, Hendar; Sujatna, Meita Lukitawati (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
The Community Service Program (PkM) aims to preserve Sundanese dance culture through the development of a dance arts curriculum at LKP Bina Lestari Sumedang. The background of this activity is the declining interest of the younger generation in traditional dance due to the influence of popular culture and the lack of relevance of the existing curriculum. The methods used include needs analysis, the development of digital-based learning modules, intensive training for educators, cultural campaigns through social media, and strengthening learning infrastructure. The results of the activity show the achievement of the new vision and mission of LKP Bina Lestari, the preparation of a structured curriculum for three levels (beginner, proficient, expert), and the creation of innovative modules that integrate cultural values and digital technology. This program also expands social impact through collaboration with art communities, cultural figures, and the surrounding community. With a collaborative approach and the utilization of science and technology, this activity has succeeded in increasing the awareness, skills, and interest of the young generation in Sundanese dance, while also strengthening local cultural identity amidst the tide of globalization.